2004
DOI: 10.1093/rpd/nch120
|View full text |Cite
|
Sign up to set email alerts
|

Development of a TL detector for neutron measurement by CaSO4:Dy phosphors

Abstract: Personal neutron dosimetry is quite a difficult area because a neutron is always accompanied with gamma radiation, which is required of a capability for mixed field dosimetry. CaSO4:Dy phosphor is known to have a very high sensitivity to gamma radiation, but the neutron capture cross section of the constituents of CaSO4:Dy are so small that the interactions between the thermal neutron and the phosphor are rare. One method to improve the neutron interaction is by introducing an impurity ion with a large thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The range of the a particle and the recoil 7 Li nucleus are of the order of a few microns in Al 2 O 3 :C. On the other hand, the range of the 3 H recoil nucleus from the 6 Li(n,a) 3 H neutron capture reaction is 23 lm in Al 2 O 3 :C and 32.1 lm in LiF. Therefore, the likelihood of secondary heavy-charged particles reaching and penetrating the Al 2 O 3 :C grain, producing OSL signal, is higher for the 6 Li(n,a) 3 H than for the 10 B(n,a) 7 Li neutron capture reaction. This is probably the explanation for the successful sensitization produced by 6 Li converters, as opposed to 10 B converters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of the a particle and the recoil 7 Li nucleus are of the order of a few microns in Al 2 O 3 :C. On the other hand, the range of the 3 H recoil nucleus from the 6 Li(n,a) 3 H neutron capture reaction is 23 lm in Al 2 O 3 :C and 32.1 lm in LiF. Therefore, the likelihood of secondary heavy-charged particles reaching and penetrating the Al 2 O 3 :C grain, producing OSL signal, is higher for the 6 Li(n,a) 3 H than for the 10 B(n,a) 7 Li neutron capture reaction. This is probably the explanation for the successful sensitization produced by 6 Li converters, as opposed to 10 B converters.…”
Section: Discussionmentioning
confidence: 99%
“…Neutron converters are used to enhance the neutron sensitivity of active and passive detectors including TLDs and image plates [6][7][8]. They interact with the neutron field through neutron capture reaction or elastic scattering, creating secondary heavy charged particles that deposit energy in the sensitive volume, the luminescence detector in this case.…”
Section: Introductionmentioning
confidence: 99%
“…For example Yang et al [14] have suggested the use of CaSO 4 : Dy TL pellets embedded with a 6 Li compound for a thermal neutron measurement. Torkzadeh and Manouchehri [15] have measured the thermal neutron fluence in a research reactor using TLD-600.…”
Section: Introductionmentioning
confidence: 99%